Systemic immune-inflammation index as a prognostic marker for chronic Hepatitis B with non-alcoholic fatty liver disease. - Xue, Bo; Wang, Zeyu; Li, Jianguo (The Journal of Infection in Developing Countries, 2025)
Introduction: This study investigates the association between high-level systemic immune-inflammatory index (SII) and cirrhosis progression in patients with chronic hepatitis B (CHB) and non-alcoholic fatty liver disease (NAFLD). Methodology: A total of 272 CHB patients with NAFLD treated at Jincheng General Hospital between January 2018 and January 2023 were included. The study endpoint was the development of cirrhosis. The optimal SII cut-off value for predicting cirrhosis progression was determined as 1024 using ROC curve analysis and Youden index. Based on this cut-off, patients were classified into low SII (n = 159) and high SII (n = 113) groups. Univariate and multivariate Cox regression analyses were performed to identify independent predictors of cirrhosis progression and assess the relationship with SII. Results: Univariate Cox analysis revealed that SII was a significant risk factor for cirrhosis progression in CHB with NAFLD (HR = 2.062, 95% CI: 1.717-3.941, p < 0.001). Multivariate Cox regression analysis demonstrated a significant association between elevated SII levels and increased incidence of cirrhosis, with patients in the high SII group having an 88.5% higher risk (HR = 1.885, 95% CI: 1.167-3.045, p = 0.010). Kaplan-Meier survival analysis further confirmed the higher risk of cirrhosis in patients with high SII levels (log-rank p < 0.001) within 60 months. Conclusions: This study suggests that SII is a relevant risk factor for cirrhosis development in CHB individuals with NAFLD, emphasizing the importance of considering SII in current clinical management.